The pharmacokinetics of codeine and its metabolites in Blacks with sickle cell disease. - Shord SS; Cavallari LH; Gao W; Jeong H; Deyo K; Patel SR; Camp JR; Labott SM; Molokie RE (European Journal of Clinical Pharmacology, 2009)
PURPOSE: We conducted a prospective, open-label study in 54 adult subjects with sickle cell disease to determine the relationship between morphine concentrations, cytochrome P450 (CYP) 2D6 genotype, and clinical outcomes. METHODS: A blood sample was obtained for genotyping and serial blood samples were drawn to measure codeine and its metabolites in the plasma before and after oral codeine sulfate 30 mg. Codeine and its metabolites were measured by liquid chromatography-tandem mass spectrometry (LC-MS). CYP2D6 genetic testing included four single nucleotide polymorphisms (SNP) indicative of three variant alleles: *17 (1023T); *29 (1659A, 3183A); and *41 (2988A) alleles. RESULTS: Thirty subjects (group I) had a mean (standard deviation) maximal morphine concentration of 2.0 (1.0) ng/ml. Morphine was not measurable in the remaining 24 subjects (group II). Nine (30%) subjects in group I and 11 (46%) subjects in group II carried a variant *17, *29, or *41 allele (p = 0.23); one (3%) subject in group I and 5 (21%) subjects in group II were homozygous for *17 or *29 allele (p = 0.07). Emergency room visits (group I 1.5 +/- 1.8 vs. group II 2.1 +/- 4.3, p = NS) did not differ based on metabolic status, but more hospital admissions (0.9 +/- 1.4 vs. 2.2 +/- 4.1, p = 0.05) were documented in patients with no measurable morphine concentrations. CONCLUSIONS: We conclude that Blacks with sickle cell disease without measurable plasma morphine levels after a single dose of codeine were not more likely to be a carrier of a single variant allele commonly associated with reduced CYP2D6 metabolic capacity; however, homozygosity for a variant CYP2D6 allele may result in reduced metabolic capacity. Furthermore, it appears that subjects without measurable morphine concentrations were more likely to be admitted to the hospital for an acute pain crisis.